Electrodeposition and speciation study of different transition metal antimonides for application into lithium ion batteries - Kershman, Jacob Ray, author; Prieto, Amy L., advisor; Elliott, C. Michael, committee member; Kipper, Matthew J., committee member (Colorado State University. Libraries, 2010)
Several new deposition setups were designed and tested to increase the uniformity of depositions of Cu2Sb. It was shown that the jacketed beaker setup produces the most uniform films compared to other setups used. This setup was used to obtain the average thickness and mass measurements of a triplicate set of films deposited at deposition times of 1, 2.5, 5, 7, and 10 minutes. The thickness (determined by AFM) and weight were both linear and corresponded to a growth rate of 300 nm per minute or 0.2 mg of Cu2Sb per minute. Preliminary battery testing revealed that the thinner films cycled much better than thicker films. Films thicker than ~1 µm did not cycle well at all, and cleaved completely off the surface of the electrode during cycling. Cu2Sb was successfully electrodeposited into commercial alumina filters. The Cu2Sb wires were ordered in a different direction compared to the electrodeposition on planar substrates ([101] versus [001] direction). A two step anodization process was shown to produce self-ordered AAO templates with pore sizes between 30 and 40 nm. It was shown that the mechanical and electrochemical polishing steps are not necessary to obtain the self-ordered templates. Promising results have been shown with multiple methods to break through the barrier layer of these alumina templates. Even when the barrier layer is removed a native oxide is formed within a few seconds on the surface of the aluminum which blocks the electrodeposition of copper. The backside of the template indicated that the breakthrough was only in localized spots. Previously, crystalline Cu2Sb was electrodeposited at single potential through the complexation of the metals in aqueous solution using citric acid at pH 6. This direct electrodeposition is unusual for intermetallic materials and the reason for the Cu2Sb case is not well understood. In order to determine why this material deposits under these solution conditions, a deeper understanding of the speciation in solution must be obtained. To study what metal-ligand complexes are present in the Cu-Sb-Citrate deposition, solution electrospray ionization mass spectrometry (ESI-MS) was employed. ESI-MS results were shown to be a qualitative technique to study the solution chemistry of the Cu2Sb system. These results have been compared to speciation calculations, UV-Vis, titrations, and literature results. The heterometallic species [CuSb(HCit)(Cit)], previously only reported in solids that had been crystallized out of solution, was discovered in solution through ESI-MS. In addition, ESI-MS data pointed to [Sb(HCit)2]- as the most abundant antimony citrate species over previously reported [SbH-1Cit]-. The additional species from ESI-MS gave rise to the development of two new balanced reactions for the deposition of Cu2Sb, in hope of the realization of understanding why Cu2Sb deposits. By understanding the solution chemistry, other transition metal antimonides were electrodeposited from aqueous citrate solutions. It is shown that through the co-deposition reaction, which is dependent on the solution chemistry and the fast interstitial diffusion of metals through antimony diffusion in the solid state, many different intermetallic antimonides can be deposited including: crystalline NiSb, the co-deposition of FeSb, and several copper-rich copper antimonide phases including Cu11Sb3, Cu4Sb, Cu0.95Sb0.05, and possibly other mixed copper antimonide phases. This leads to a better understanding of the electrodeposition of the Cu2Sb system, which can lead to further improvement of the electrodeposition other transition metal antimonides and intermetallics.
Keywords: intermetallic; ESI-MS; copper antimonide; electrospray ionization mass spectrometry; electrodeposition; Antimony alloys; Copper alloys; Alloy plating; Electrospray ionization mass spectrometry